Evolution of confined species and their effects on catalyst deactivation and olefin selectivity in SAPO-34 catalyzed MTO process. Issue 21 (11th February 2016) - Luo, Mingjian; Zang, Hongyan; Hu, Bing; Wang, Baohui; Mao, Guoliang
Abstract : A "three sections, three periods" mechanism is proposed to discuss the formation and transformation of confined species and its effects on catalyst deactivation and product selectivity. Abstract : Confined species in SAPO-34 cages participate in methanol reaction and affect product selectivity as well as leading to the deactivation of the catalyst during the MTO process. In this work, spatial- and time-evolution of the confined species in a fixed bed are investigated by TG and dissolution–extraction experiment. Results indicate that both methanol and olefins lead to the formation of confined methylbenzenes and methylnaphthalenes, which are active intermediates in the MTO process. These intermediates further transformed into phenathrene and pyrene in the methanol reaction section and led to the deactivation of the catalyst. A pseudo-steady state period, during which selectivities of products are relatively stable, is achieved while most of cages are occupied by naphthalene and methylnaphthalenes. Confined species reduce the cage volume for products and reactants and thus affect product selectivities. Empty cages are likely to form relatively large-size products like C4 and C5+ molecules. Cages occupied by large-size methylnaphthalenes tend to form more ethene, less propene and even less C4+ products than those occupied by relatively small methylbenzenes. Simultaneously, secondary reactions of olefins, which increase the formation of alkanes and C4+ products during the initiation period, are greatly reduced in the pseudo-steady state period since olefins are hindered from entering occupied cages. As a result, ethene and propene selectivities and C2 /C3 ratio tend to increase while C4+ and alkane selectivities decrease with the prolonging of time on stream.